2004
DOI: 10.1021/ic0492690
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Discotic Uranium-Containing Liquid Crystal

Abstract: The synthesis of several UO(2)-alaskaphyrin derivatives functionalized with aliphatic chains is described. These compounds are found to be liquid-crystalline and form columnar mesophases, as judged from polarizing optical microscopy studies, and represent the first uranium-containing discotic mesogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…On the other hand, several actinide-containing Schiff base macrocycles have been reported by our group [4,[15][16][17][18]. Among these, perhaps the best studied has been 'alaskaphyrin' (2), a 2,5-diformylpyrrolederived Schiff base system that is characterized by its ease of synthesis and its robustness [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several actinide-containing Schiff base macrocycles have been reported by our group [4,[15][16][17][18]. Among these, perhaps the best studied has been 'alaskaphyrin' (2), a 2,5-diformylpyrrolederived Schiff base system that is characterized by its ease of synthesis and its robustness [15].…”
Section: Discussionmentioning
confidence: 99%
“…In light of these attributes, we are working to develop this system as a platform for the generation of actinide-containing liquid crystals. In the first part of this paper, we describe the preparation and characterization of an initial set of uranyl-based alaskaphyrin liquid crystals [18]. In the second part of the paper, the synthesis of new actinide complexes derived from other Schiff base pyrrolic macrocycles is detailed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we reported the first discotic liquid crystals based on expanded porphyrins. [40][41][42] The first of these, a system called hydrazinophyrin, was characterized as a free base and was found to exist as a columnar mesophase as judged from polarizing optical microscopy. [40] A second liquid crystalline system was obtained by preparing the uranyl complexes of a hexaazamacrocycle called alaskaphyrin.…”
Section: Introductionmentioning
confidence: 99%
“…[40] A second liquid crystalline system was obtained by preparing the uranyl complexes of a hexaazamacrocycle called alaskaphyrin. [42] Both of these mesogens were Schiff-base derived and hence inherently susceptible to hydrolytic instability. Recently, however, we found that mesomorphic behavior could also be induced in appropriately substituted cyclo [8]pyrroles by addition of electron-acceptor molecules, such as polynitroaromatics.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we are aware of only two expanded porphyrin mesophases: both are derived from imine-linked oligopyrrolic macrocycles and neither is aromatic. [14][15][16] We have thus sought to produce a liquidcrystalline mesophase based on an all-carbon-linked, aromatic expanded porphyrin framework and report here the synthesis of new cyclo [8]pyrrole derivatives 1 a-c that form hexagonal columnar (Col h ) mesophases when combined with electron-deficient acceptors, such as trinitrofluorenone (TNF), trinitrobenzene (TNB), trinitrophenol (TNP), and trinitrotoluene (TNT). The resulting systems are structurally interesting because of the presence of hydrogen-bonded sulfate ions.…”
mentioning
confidence: 99%